Learning Space for Libraries in the 21st Century: Perspectives from the Center for Library Resources and Educational Media, Walailak University - Sangkaew, Nattagan; Leeniva, Pasit (วารสารสถาปัตยกรรม การออกแบบและการก่อสร้าง, 2025)
This study aimed to explore the need for collaborative spaces in libraries and provide practical guidelines for their design and usage. Data were collected from 17 interviewees and 168 survey respondents who shared perspectives on enhancing 21st-century skills. Based on the findings, the study proposed recommendations for designing shared spaces in libraries, including meeting rooms, group work areas, computer desktop zones, and service points for snacks and beverages. Three key design principles emerged: zoning, flexibility, and creating a creative environment. These principles offer a comprehensive framework for designing collaborative spaces that meet diverse needs and foster active, engaged learning. Libraries are evolving into vibrant learning environments, and these guidelines provide valuable insights for designing collaborative spaces that cater to evolving demands. The recommended design elements include meeting rooms, group work areas, computer desktop zones, and service points for snacks and beverages. The design principles emphasize clear spatial separation, flexibility, and fostering a creative environment. Implementing these suggestions transforms libraries into hubs of collaboration and active learning. This research provides valuable insights and recommendations for designing collaborative spaces in libraries, enabling them to play a crucial role in supporting learning and skill development for users. Libraries should adapt to meet evolving needs, with an emphasis on creating spaces that foster collaboration and creativity, including diverse areas, and designated zones for quiet and privacy. Continuously enhancing these spaces will help libraries stay current and responsive to evolving user needs.